The War Against Ukraine and the EU
XIII, 230 p. 10 illus., 5 illus. in color.
Keywords: “Russia’s invasion of Ukraine in 2022 has fundamentally challenged the EU’s political, legal and economic foundations. What will be its impact on the EU (and EU studies), not only in the short-, but also mid- and long-term? This book provides all the relevant answers, expressed in clear analytical terms and supported by abundant empirical evidence. A crucial contribution to the debate about the future of Europe.” —Federica Bicchi, The London School of Economics and Political Science “The War against Ukraine: the EU facing new realities examines the consequences of Russia’s war on Ukraine for the process of European integration and the practice of the study of Europe. Bringing together a superb collection of contributors, the volume challenges past thinking while opening new avenues for explaining and understanding the new landscape for European foreign policy.” —Richard G. Whitman, University of Kent This open access book aims at discussing the manifold consequences that the War against Ukraine bears for the European Union and EU Studies. It takes stock of the fact that the Russian Attack on Ukraine and the ensuing War not only affects the Global Order, but also has challenged a number of established narratives and convictions for the European Union and its member states. The EU now needs to position itself in the changing world order. Concretely it needs to deal with a number of membership applications, internal and external challenges to liberal democracy, and the development of its strategic autonomy in a number of decisive policy fields. The book convenes experienced scholars, with chapters covering the following themes and fields: Theories, approaches and concepts in EU studies and IR; the EU and the changing European and Global Order; the War and defence of liberal democracy; Membership Politics; Energy Policy. Claudia Wiesner is Jean Monnet Chair and Professor of Political Science at Fulda University of Applied Sciences, Germany. Michèle Knodt is Jean Monnet Chair (ad personam) and Professor of Political Science, TU Darmstadt, Germany.